Potentiation of immune checkpoint blockade with an ITPP radiosensitizer studied with oxygen saturation measurements from photoacoustic imaging - Renee L. Tran; Xiaofei Liang; Jorge de la Cerda; F. William Schuler; Mark D. Pagel (Scientific Reports)
Abstract Hypoxia in the tumor microenvironment hinders antitumor immunity. Increasing tumor oxygenation may promote T cell infiltration and tumor control by immune checkpoint blockade (ICB). We found that a radiosensitizer, myo-inositol trispyrophosphate (ITPP), caused oxygen unloading from hemoglobin in CT26 and 4T1 tumors as indicated by photoacoustic imaging (PAI). This change in hypoxia detected by PAI was correlated with strong positive correlations with CD8+ and CD4+ FoxP3- effector T cell (Teff), and negative correlations with monocyte frequencies, indicating that ITPP promoted more immunogenic tumor microenvironments in both models. Combination ITPP and ICB improved tumor control and survival in both models. Therefore, imaging ITPP-modulated tumor hypoxia with PAI was related to ICB treatment response in these studies. Future combination immunotherapy regimens may benefit from monitoring hypoxia using molecular imaging with PAI.